Analyzing the microfoundations of human violence in the DRC - intrinsic and extrinsic rewards and the prediction of appetitive aggression - Haer, Roos (BioMed Central, 2013)
BACKGROUND: Civil wars are characterized by intense forms of violence, such as torture, maiming and rape. Political scientists suggest that this form of political violence is fostered through the provision of particular intrinsic and extrinsic rewards to combatants. In the field of psychology, the perpetration of this kind of cruelty is observed to be positively linked to appetitive aggression. Over time, combatants start to enjoy the fights and even the perpetration of atrocities. In this study, we examine how receiving rewards (intrinsic versus extrinsic) influence the level of appetitive aggression exhibited by former combatants. METHOD: We surveyed 95 former combatants in the eastern provinces of the Democratic Republic of the Congo. RESULTS: Linear regression analyses reveal that intrinsic as well as extrinsic rewards are linked to the former combatants’ Appetitive Aggression score. However, this relationship is partly determined by the way in which combatants are recruited: While abducted combatants seem to react more strongly to extrinsic rewards, the score of those that joined voluntarily is primarily determined by intrinsic rewards. CONCLUSIONS: We conclude that receiving rewards influence the level of appetitive aggression. However, which type of rewards (intrinsic versus extrinsic) is of most importance is determined by the way combatants are recruited.